The social and behavioral effects of home quarantine in the Covid-19 pandemic on a sample of married female students at the University of Sharjah - Abdallah, Rania; AlMedani, Khalil (Al-Adab Journal, 2024)
This study aimed to identify the effects of home quarantine on the family. The study was applied to a sample of female students from the University of Sharjah, with the aim of identifying the negative social and behavioral effects on the family.            The study was conducted on a sample of (118) married female students at the University of Sharjah, Department of Sociology, through designing a questionnaire and conducting a direct interview with (12) 12 families live in Sharjah.The study includes three chapters, the first chapter deals with the problem of the study, the second chapter deals with theoretical trends and previous studies, and the third chapter deals with the field study and data analysis.Among the most important findings of the study are: The conditions of home quarantine and social distancing were not completely suitable for children's education. Less communication with relatives and friends As a result of that stone, there was great difficulty in reconciling family and academic situations. Addictive behavior appeared on the use of social media for both spouses. The spouses and children became afraid of grocery items, and they resorted forcefully and sterilized them constantly. The behavior of mood swings and nervousness was one of the biggest problems that all family members faced, as the study showed. Sleep disruption is the most dangerous for children.